Peningkatan Kemampuan Pembukuan Sederhana Bagi WPOP Pedagang Eceran Kriteria Usaha Mikro Kota Semarang - Nuria Universari; Lulus Prapti, N.S.S; Rosyati; Totok Wibisono (AMMA : Jurnal Pengabdian Masyarakat, 2022)
The focus of this PkM activity is more focused on the problem of not implementing financial bookkeeping practices for Retail Traders as Individual Taxpayers with Micro Business Criteria in Semarang City. The solution offered in PkM activities is to provide simple financial bookkeeping training. The target of service activities is awareness of PkM partners about the importance of doing simple bookkeeping and increasing knowledge and understanding of simple financial bookkeeping. The method of activity is training by providing simple financial bookkeeping materials. After that, an evaluation was held by giving a pretest and posttest to find out the differences in participants' understanding of simple financial bookkeeping before and after the training, as well as giving a questionnaire to determine the participant's assessment of the implementation of Community Service. Through this PkM activity, simple bookkeeping training participants are increasingly aware of the importance of simple bookkeeping. In addition, they know and understand more about simple financial bookkeeping that should be carried out by taxpayers.